(untitled) (Journal of Philosophy Culture and Political Science, 2022)
Within the framework of cooperation between the Republic of Kazakhstan and the Russian Federation, problems affecting the security of their border territories are being considered. Relations between the two countries in the field of cross-border cooperation are an important part of interstate policy. The land border between our countries is the longest in the world. This makes it possible for effective cooperation in such areas as industry, trade, military-technical sphere and other areas. The specifics of Kazakh-Russian cross-border cooperation, existing priorities and areas of activity are among the urgent problems that are of great scientific and practical interest. Both states have the necessary political will, which allows them to fully develop promising areas of cooperation: industrial cooperation, joint use of natural resources, development and implementation of innovative and scientific and educational projects, as well as ensuring the security of border territories. The main purpose of the study is to identify ways to improve Russian-Kazakh cross-border cooperation based on the analysis of its state, development trends and key problems that negatively affect the interaction of neighboring regions. The main research methods used are general scientific methods, such as logical analysis, synthesis, ascent from the abstract to the concrete, historical, comparative methods and the method of descriptive-inductive analysis of formal legal institutions. The article examines the history of cross-border cooperation between Kazakhstan and Russia. The analysis of those problems at the border that are a threat to the security of territories and the population is given, and the activities of the border service of Kazakhstan are also considered. Keywords: cross-border cooperation, neighboring countries, border, security, border territories, population, development, border service, drug trafficking, smuggling.